THE MORAL PHILOSOPHICAL ANALYSIS AS REFLECTED ON DAN BROWN’S INFERNO - Dwita Laksmita Rachmawati; Fabiola Dharmawanti Kurnia; Ali Mustofa (Universitas Muhammadiyah Makassar, 2020)
Moral philosophical is central to philosophy study as most issues have been discussed in the philosophy that related to morality. People who are not familiar with the other philosophical belief would think that the other party's belief is wrong while they hold the truth. This issue can be found in any social problem and has been reflected in one of literature work. A literature product is the closest portrait which reflects society's real situation and cultural background, including moral and ethnicity; one example of the products is Dan Brown’s Inferno. In the novel, Brown portrays that there are two sides to the philosophical belief of the truth, which exist in a society. Two main characters reflect the two different beliefs of truths; Bertrand Zobrist versus Dr. Langdon and society. This article uses intentionality theory, which is proposed by Husserl to do moral philosophical analysis critically in order to examine how two sides of philosophical views are believed by two types of parties, society, and Zobrist. To support the analysis, the writer uses philosophy of mind as the primary theory to analyze the moral perspective. The result shows that Zobrist has his own belief that killing half of the human population by bombing them is the right thing to do to save the world. His belief has been built as he is conveyed by Inferno, one of Dante’s great work. Meanwhile, Dr. Langdon and society think that Zobrist’s belief is wrong; his action and plan to kill people is inhuman